Pengaruh Disiplin, Motivasi, Budaya Organisasi dan Stres Terhadap Kepuasan Kerja Pendidik di Kabupaten Brebes - Sulaefi, Sulaefi (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2018)
This is research aims to influenceÃ‚Â of Ã‚Â work discipline, motivation, organizational culture, and work stress on public teacherÃ¢â‚¬â„¢s job satisfaction at the Public High SchoolÃ‚Â at Brebes District . ThisÃ‚Â researchÃ‚Â was conducted in four Public High School. Primary data by the method of survey with questionnaires from 100 responden to the scale Likert with hypothesis used this research.Ã‚Â The techniques of processing and analysis data used linear regression analysis.Ã‚Â Ã‚Â Result of the analysis performed revealed that there are positive effect of variable work discipline of teacher Ã¢â‚¬Ëœs job satisfaction positive influence motivational variable of teacherÃ¢â‚¬â„¢s job satisfaction, positive influence on organizational culture variables job satisfaction of the teacher, negative effect of work stress variables on teachers job satisfaction and positive influence of work discipline, motivation, and organizaonal culture stress work simultaneously on teacherÃ¢â‚¬â„¢ job satisfaction.